2015
DOI: 10.1108/pijpsm-05-2015-0066
|View full text |Cite
|
Sign up to set email alerts
|

Police transformational leadership and organizational commitment

Abstract: Purpose – The purpose of this paper is to explore whether the relation between police transformational leadership and organizational commitment is mediated by organizational culture. Drawing on the competing values framework (Quinn, 1988), four types of cultural orientations (group, developmental, hierarchical, and rational) are analyzed. Design/methodology/approach – In total, 358 South Korean police officers are surveyed. Using competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 58 publications
2
46
0
9
Order By: Relevance
“…Brewer and Clippard (2002) discussed that organizational culture is a significant tool for improving organizational commitment. Shim et al (2015) showed that officers committed to group culture are more committed to their organizations. Messner (2013) also suggested that there is a positive relationship between organizational culture and organizational commitment, and it also recommend designing a corporate culture change strategy in order to increase organizational commitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brewer and Clippard (2002) discussed that organizational culture is a significant tool for improving organizational commitment. Shim et al (2015) showed that officers committed to group culture are more committed to their organizations. Messner (2013) also suggested that there is a positive relationship between organizational culture and organizational commitment, and it also recommend designing a corporate culture change strategy in order to increase organizational commitment.…”
Section: Discussionmentioning
confidence: 99%
“…One study applied to the Turkish logistics industry surveyed 344 employees, with the results showing that there is a positive relationship between organizational culture and organizational commitment (Acar, 2012). Shim, Jo, and Hoover (2015) showed that officers that were committed to a group culture were more committed to their organizations, with the study applied to 385 Korean police officers. Messner (2013) also found that there was a positive relationship between organizational culture and organizational commitment, recommending the design of a corporate culture change strategy, in order to increase organizational commitment in India's IT services.…”
Section: Organizational Culture and Organizational Commitmentmentioning
confidence: 99%
“…Similarly, other findings posited that a positive and partial mediation effect of hierarchical culture on the relationship between leadership and organizational change management (Al-Ali, Singh, Al-Nahyan, & Sohal, 2017). In another study conducted which aims at exploring whether the relation between police transformational leadership and organizational commitment is mediated by organizational culture, it was realized that transformational leadership and commitment appear to be fully mediated by group culture (Shim, Jo, & Hoover, 2015). Findings of a research conducted by Arif, Zahid, Kashif, & Ilyas Sindhu, (2017) also depicts that there exist significant and positive nexus between leader-member exchange and organizational change management as well as organizational culture show mediation between LMX and organizational change management.…”
Section: Mediating Role Of Organizational Culturementioning
confidence: 99%
“…Chen et al (2016) menyatakan bahwa kepemimpinan transformasional cenderung menduduki posisi sentral dalam saran internal sehingga mereka terhubung langsung dengan hampir semua anggota tim untuk mentransmisikan tujuan, mengantisipasi masalah, meminta saran, dan pengelolaan arus sumber daya, kepemimpinan transformasional yang di miliki oleh seorang manajer hendaknya dapat menciptakan integrasi yang tinggi dan mendorong gairah kerja karyawan itu sendiri. Shim et al (2015)…”
Section: Pendahuluanunclassified